NEGOTIATION THEORY AND ECOLOGICAL AWARENESS REPRESENTED IN RAYA AND THE LAST DRAGON MOVIE - Muninggar, Afifah Retno; Kurniawan, Muhammad Hafiz (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The aims of this paper are to identify how negotiation theory can be used to raise ecological awareness in Raya and The Last Dragon movie. This movie is an animated picture that truly brings the culture of Southeast Asia into life while it aesthetically pleases the viewer because of the magnificent story and graphic. In analyzing data, this research applies the theory of Eco-criticism proposed by Abraham and Jayemanne. The data are in forms of verbal and non-verbal data. After the data are analyzed, they are described descriptively by using negotiation theory proposed by J. R Martin and David Rose including mood, speech function, and exchange structure. This research is a descriptive qualitative method. The data number of this research is 241 consists of clauses, phrases and sentences from the conversation. As the result, this research highlights the importance of understanding the MOOD structure and the relationships between characters in the film to raised ecological matters in Raya and The Last Dragon Movie. This research finds that declarative clause appears 112 times as dominant mood structure, and 30 times these declarative clauses are used to depict the ecological awareness such as mentioning the importance of maintaining natural balance over interest which harms nature.